The Use Of Control Suture In Cleft Lip Surgery - Sudjatmiko, Gentur; Ramadan, Mohamad Rachadian (Jurnal Plastik Rekonstruksi, 2012)
To achieve an optimal result in cleft surgery, executing the proper designs and precise techniques are mandatory. Several techniques are proposed for the repair of unilateral and bilateral cleft lip. In 1955, Millard !rst described the techniques of advancing a lateral upper lip "ap combined with downward rotation of the medial segment.1 From experience, the above- mentioned technique may be modi!ed to facilitate better lip rotation and symmetry. Technically, it also provides a more ef!cient work"ow and more accurate results. All efforts in lip repairs have one ultimate goal, which is to achieve corrected lips with minimal scar and as much resemblance to that of the normal lips: by anatomy, symmetry, and muscle function.